Environmental strategy, management accounting, proactivity and performance in ISO14001-certified companies in Malaysia - Appannan, Jeya Santhini (2020)
The world is facing a multitude of environmental problems, ranging from biodiversity loss, environmental pollution, deforestation and climate change. Many environmental problems are resulting from human activities that eventually either drive or trigger environmental catastrophes. Similarly, in Malaysia, environmental pollution is expected to become worse as the result of massive economic growth and rapid urbanisation. Given the overwhelming concerns on environmental issues, this study attempts to investigate the effect of environmental strategy, with a focus on important role of environmental management accounting on environmental performance. Additionally, this study also examines the moderating effect of environmental proactivity that was largely ignored in previous studies, on the relationship between environmental management accounting and environmental performance. This study embedded both the theory of Natural Resource-Based View (NRBV) and Dynamic Capabilities (DC) in testing the link between environmental strategy, environmental management accounting, environmental proactivity, on environmental performance. The NRBV offers a connection between the natural environment with firms’ resources and performances. On the other hand, theory of Dynamic Capabilities offers capabilities to enable firms to effectively initiate, search and execute and renew its innovative activities. In view of lack of empirical studies in this area, as well as to respond to calls of previous researchers, this study has employed important capabilities emerged from environmental management accounting and environmental proactivity to be integrated into the NRBV to enhance firms’ environmental performance. The target population consisted of ISO 14001 certified companies in Malaysia drawn from listing provided by SIRIM QAS International Sdn. Bhd. Systematic sampling method was applied. A total of 145 responses were collected from managers of ISO 14001 certified companies in Malaysia and the data was subjected to a structural equation analysis using Smart PLS version 3.2.7 software. This study found that the pollution prevention strategy and the clean technology strategy possess a significant positive relationship with environmental management accounting. Furthermore, the results of PLS-SEM revealed that environmental management accounting had a mediating relationship between pollution prevention strategy and clean technology with environmental performance. These findings indicate that environmental management accounting is a useful and important system in providing information to attain better environmental performance in Malaysia firms and the outcomes are also suitable for companies operating on other emerging countries in terms of developing capabilities to be able to manage EMA system and as a consequence, to improve environmental performance. Unfortunately, the findings failed to confirm any support for the argument that process stewardship influences environmental management accounting, nor does the environmental management accounting show its mediating effect on the relationship between process stewardship and environmental performance. Additionally, this study also found that environmental proactivity positively moderates the relationship between environmental management accounting and environmental performance. This result seems to indicate that, high level of voluntary action in environmental proactivity together with its flexible capabilities will result in high use of environmental management accounting that plays an important role in determining a better firm’s environmental performance. This findings further illustrate that ISO 14001 certified companies in Malaysia are now moving beyond meeting the basic regulatory requirement by engaging with EMA at more sophisticated level to improve environmental performance. Furthermore, this study offers novel insights that extends the existing literature concerning the outcomes of environmental management accounting and environmental proactivity within the context of environmental management studies. To improve the generalization of the findings, future research should broaden the sample to non ISO 14001 certified companies in Malaysia. This paper also contributes to a deeper understanding that environmental management accounting requires increasing environmental knowledge and generating a wider conception of environmental management throughout organization, as such government agencies have to play a significant role in promoting environmental management accounting as well as encourage companies to engage more in environmental programmes in order to increase their level of proactivity.